FROM HOLISTIC SUSTAINABILITY TO INTEGRATED PLANNING - Tsvetanova, Maria (E-Journal VFU, 2025)
The research compares the public (urban) and corporate spheres. In the public sphere, the concept of smart cities imposes the integration of non-financial indicators and DSS for effective territorial planning. In the corporate context, integrated reporting serves as a framework for connecting financial performance with non-financial (sustainable) management and long-term value creation. Business Intelligence (BI) is established as a universal tool. BI transforms heterogeneous data (from sensors, ERP or DSS) into operational variants and visualized KPIs that support decision-making. The article emphasizes the convergence of information needs and the critical role of BI as an analytical bridge between ESG requirements and effective planning.